PEREMPUAN DALAM PANDANGAN AHMAD TOHARI: KAJIAN SOSIOLOGI SASTRA TERHADAP NOVEL BEKISAR MERAH - NFN Uniawati (Balai Bahasa Sulawesi Tengah, 2014)
Ahmad Tohari through novel he wrote, Bekisar Merah, poured his critic against the female roles assigned by common convention in community. This paper aims to gain an understanding of the overall self-image of women based on social aspects described Ahmad Tohari through Bekisar Merah. The Data analyzed in the form of phrases, words, and sentences which are related through theevents that involve directly the main character, displaying a named woman called Lasi. The data taken from novels Bekisar Merah by Ahmad Tohari. Methods used in analysis sociology literature. The result of the analysis shows that the women imaged by author through Lasi not entirely free being personal out of female concepts according to culture that shape it. Nevertheless, the other authors describe its refusal to the traditional society assumption that women are always inferior than men. Women as well as men have social roles which can change the traditional roles that are positive.